Selenium and iodine sorption and fixation on calcareous soils from Somalia - Ali, I.R. (2020)
Knowledge of the geochemical behaviour of selenium (Se) and iodine (I) in the calcareous and gypsiferous soils of Somalia is critical to a better understanding of their implications for human health. In particular, it is important to understand the effects of soil-type and sources of drinking water and irrigation water on Se and I provision to the human diet. Though dietary Se inadequacy is widespread in Africa (22%), no data is available for Somalia yet. Thus, this study aimed to understand and describe, for the first time, the soil-plant-water Se status and trace the causes of excess iodine reported in Somalia using a geo-nutrition approach. In addition, the study aimed to investigate the effect of soil properties on total Se and I concentrations, speciation and extractability in Somali agricultural soils. Samples of topsoil (n=12, 15 cm depth) were collected from rainfed and irrigated fields in Somalia and analysed for several trace elements (TEs) including Se and I. In addition, crops, which included maize (Zea mays L.), cowpea (Vigna unguiculata L.) and mung bean (Vigna radiata L.), and samples of their corresponding soils were collected from several farms (n=9). The Se and I concentrations of the surface water and groundwater samples were also measured. The results showed that Se deficiency is more likely to be prevalent in Somalia based on the Se status of agricultural soils (mean: 400 µg kg-1), crops (Cow pea: 158 µg kg-1; Mung bean: 41.7 µg kg-1; and maize: 16.7 µg kg-1), surface water (0.595 µg L-1) and groundwater (3.63 µg L-1). The total I concentration in groundwater (median: 990 g L-1) is consistent with the high urinary iodine contents reported in literature, revealing that drinking water was a greater source of excess iodine than iodised salt. Only the labile fractions of trace elements within the soil’s rooting zone have the potential to be taken up by plants. Therefore much of the current study focussed on assessing the reactive forms of both Se and I in Somali soils and investigating the speciation of both elements. A three-step sequential extraction scheme was employed for the soil Se and I fractionation adapted to distinguish the operationally defined “soluble”, “adsorbed”, “organically bound” and recalcitrant fractions. The sequential extraction procedures applied to Somali agricultural soils demonstrated the presence of a large non-extractable Se pool, especially in carbonate-rich soils. Thus, the calcareous soil minerals (i.e. calcite and gypsum) are hypothesised to influence the dynamics of the Se and I species. This hypothesis is supported by the correlation between the residual Se and the CaCO3 content of the soils. Therefore, the field survey was augmented by batch trials that examined the following: i) the interaction between Se species and calcareous minerals; ii) the interaction between I species and these pure phases. The adsorption-desorption and fixation of Se and I on calcite/gypsum was investigated in a series of batch adsorption experiments covering a wide range of initial concentration ranges (5 µg L-1 – 5 mg L-1), species (selenite, selenate and iodate) and contact times (from 1 to 21 days). Selenium sorption results revealed that the degree of Se sorption is dependent on the Se species and the solid phase. Selenium adsorption on gypsum (mean Kd value 4.60) was lower than that of calcite (mean Kd value 30). Both minerals showed greater affinities for selenite when compared to selenate. Adsorption of freshly added I (e.g. in irrigation water or rainfall) on calcite occurred rapidly (< 24 hours) with no evidence of consistent time-dependent sorption. However, desorption hysteresis for both Se and I was seen. In addition, stable isotopic Se (77Se) and radioactive iodine (129I) techniques were applied, using isotopic exchange principles, to determine the ‘labile’ pool of Se and I. Results from the batch adsorption and isotopic dilution experiments were supported by an EXAFS study aimed at understanding the Se bonding mechanisms on calcite, gypsum and calcareous soils. The EXAFS results indicated that selenite forms inner-sphere complexes on these minerals.